PENGARUH PENGETAHUAN PERPAJAKAN DAN KUALITAS PELAYANAN PAJAK TERHADAP MOTIVASI WAJIB PAJAK ORANG PRIBADI DALAM MEMENUHI KEWAJIBAN PERPAJAKAN (Studi Kasus KPP Pratama Pekanbaru Tampan) - Sari, Reski Purnama; Gusnardi, Gusnardi; Gimin, Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to know the influence of taxation knowledge and quality of service tax on the motivation of individual taxpayers in fulfilling the tax obligations in KPP Pratama Pekanbaru Tampan. The population in this study is the entire taxpayer of the private person registered in KPP Pratama Pekanbaru Tampan ie as many as 169,059 persons taxpayers personally and on this research the sampling used is non probability sampling With incidental sampling techniques. To determine the size or number of samples from the population use the formula Slovin with an error rate of 10%. According to the formula Slovin with an error rate of 10%, if the population in this study amounted to 169,059, then the sample amounted to 100 individual taxpayers. Data is collected using questionnaires on taxation knowledge, quality of tax services, and the motivation of taxpayers distributed to respondents. Data analysis uses multiple linear regression test data analysis. The results concluded that the knowledge of taxation and the quality of tax service has significant effect on the motivation of individual taxpayers in KPP Pratama Pekanbaru Tampan. It is hoped that KPP Pratama Pekanbaru Tampan can consider the quality aspects of tax services and other aspects that are not researched in this to increase the motivation of taxpayers in fulfilling the tax obligations. In the event of an increase in taxpayer motivation, this will have a good impact on increasing the tax revenues that will impact the increase in regional and state revenues.Key Words: knowledge of taxation, quality of service tax, and motivation for taxpayers.